La noción de significado convencional en la interfaz semántica–pragmática (Contribution to the lexical-semantic study of the verb ponerse) - Noguerol, Maria Eugenia Conde (Universidad de Cadiz, 2018)
This work is a contri-bution to the lexical-semantic study of the verb ponerse as a sup-port verb for the expression in Spanish of a change of state affect-ing animated entities. From its combinatorial study and occur-rences in the CREA, we have been able to group the different attrib-utes with which this verb com-bines and establish well-defined semantic classifications that, to-gether with other semantic-syn-tactic criteria, such as the actatial structure, the syntactic structure and the point of view or focus, have allowed us to draw conclusions about the actual behaviour of the verb ponerse. Due its aspectual complexity, we have taken into account semantic, syntactic and contextual aspects. In addition, in some occasions we have resorted to pragmatic factors that, though having no grammati-cal relevance, have helped to ob-tain a more exhaustive interpreta-tion. As we will see, ponerse is then a support verb that allows the ex-pression of changes of state that affect the physical state, the psy-chic state and the human behav-iour or disposition.